2018
DOI: 10.1016/j.ijpsycho.2018.04.006
|View full text |Cite
|
Sign up to set email alerts
|

ERP evidence for implicit L2 word stress knowledge in listeners of a fixed-stress language

Abstract: Languages with contrastive stress, such as English or German, distinguish some words only via the stress status of their syllables, such as "CONtent" and "conTENT" (capitals indicate a stressed syllable). Listeners with a fixed-stress native language, such as Hungarian, have difficulties in explicitly discriminating variation of the stress position in a second language (L2). However, Event-Related Potentials (ERPs) indicate that Hungarian listeners implicitly notice variation from their native fixed-stress pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 60 publications
1
5
0
Order By: Relevance
“…Therefore, 30 participants remained in the final sample (19 females). The participants, aged between 18 and 25 years ( M Age = 21.7 years, SD = 1.6 years), were native speakers of Hungarian who have not studied German as L2 according to a questionnaire screening their linguistic background (Kóbor et al, ). All of them were right‐handed according to the Edinburgh Handedness Inventory revised version (Dragovic, ) ( M LQ = 90.4, SD = 12.9).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, 30 participants remained in the final sample (19 females). The participants, aged between 18 and 25 years ( M Age = 21.7 years, SD = 1.6 years), were native speakers of Hungarian who have not studied German as L2 according to a questionnaire screening their linguistic background (Kóbor et al, ). All of them were right‐handed according to the Edinburgh Handedness Inventory revised version (Dragovic, ) ( M LQ = 90.4, SD = 12.9).…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, in other languages it is fixed, occurring consistently on specific syllable loci. Although speakers of languages without contrastive lexical stress (e.g., French, Hungarian, Welsh) often experience difficulty consciously discriminating between the stress patterns of languages with variable stress [25,26], a host of EEG experiments have revealed that such 'stress-deaf' individuals still shown brain sensitivity to stress violations, and in particular to violations of native fixed stress patterns [27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Again, ERP and reaction time data recoded in word onset priming appear to dissociate functionally different aspects of speech processing and decision making. While ERP reflected privileged processing of partially mismatching targets (compared to unrelated targets) across several studies with adults, decision latencies for partially mismatching targets were not facilitated in some studies (Friedrich et al, 2008;Schild et al, 2014a;Kóbor et al, 2018) or even inhibited in one study (Friedrich et al, 2013). That is, in former studies, processing reflected in the ERP was more tolerant to subtle phonological variation than processing reflected in lexical decision latencies.…”
Section: Can Previous Findings On Phonologicalmentioning
confidence: 92%
“…For pre-readers, ERP did not differ between both conditions. The authors related ERP differences between the Identity and the Variation condition in readers to the leftanterior P350 emerging between 300 and 400 ms after target word onset in adults (Friedrich, 2005;Friedrich et al, 2008Friedrich et al, , 2009Friedrich et al, , 2013Bien et al, 2014;Schild et al, 2014b;Kóbor et al, 2018;Schild and Friedrich, 2018). For adults, P350 effects in word onset priming reflected fine-grained mapping between the input and lexical representations (e.g., Friedrich et al, 2009;Schild et al, 2012).…”
Section: Introductionmentioning
confidence: 99%